Materialkultur og territorialbevidsthed i Acta - Lederballe Pedersen, Thomas (Dansk Teologisk Tidsskrift, 2011)
Material culture either upheld or established by authorities within the Roman empire can be interpreted as vehicles for describing the territorial expansion of Christianity in the Acts of the Apostles. Acts 17:16-34 and 18:24-19:40 display an emphasis on the role played by material culture, notably images in Athens and Ephesus, in defining urban political and cultural centres. Roman material culture also sheds light on the metaphorical meaning of the recurrent expression “the way” in Acts. Acts 8:26-40 provides indications of this, suggesting that the meaning of the expression is informed by the ubiquitous road system in the Roman empire and by the symbolic and metaphorical significance of the roads in describing Roman territory.